La percepción emocional del dinero como determinante de un comportamiento de ahorro o endeudamiento - Ma. Carmen Lozano Gutierrez; Federico Fuentes Martín (Colegio de Economistas de A Coru\~na, 2007)
– Presently article is carried out an analysis of affinities in the money perception for people that save or get in debt, in order to know the consequences that have the subjective valuations in relation to the money in the economic behavior characteristic of each group settling down. The conclusions we arrive could be good for the development of strategies of saving promotion and indebtedness contention.
Keywords: 330; Verhaltensökonomik; Sparen; Schulden